Konstruksi Kurikulum Body Safety Berbasis Teologi Tubuh Dan Imago Dei Bagi PKAUD - Pidemon Gulo; Melfin Wulandrari Gulo (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2026)
Body safety education is a vital component of preventing sexual violence against young children, yet its application in Christian early childhood education often remains fragmented and insufficiently connected to theological anthropology and institutional safeguarding. This study constructs a body safety curriculum grounded in the theology of the body and Imago Dei for Christian early childhood education. It employs a qualitative-conceptual approach through an integrative literature review and constructive theology, examining national and international journal articles published from 2016 to July 2026. The literature was analyzed by conceptual mapping, thematic categorization, interdisciplinary theological dialogue, and curriculum synthesis using backward design. The study produces the IMAGO-SAFE model, which integrates bodily dignity, anatomical and privacy literacy, child agency and boundaries, protective actions, trusted adults, safe and confusing situations, anti-secrecy and anti-grooming education, family-school-church safeguarding, and authentic inclusive assessment. The model is operationalized into eight play-based learning units. The study concludes that body safety education must strengthen children's protective competencies without transferring primary responsibility from adults and institutions to children.